A molecular phylogeny of carcinoecium-forming Epizoanthus (Hexacorallia: Zoantharia) from the Western Pacific Ocean with descriptions of three new species - Hiroki Kise; Javier Montenegro; Merrick Ekins; Takeya Moritaki; James Davis Reimer (Systematics and Biodiversity, 2019)

The role of renewable energy in climate stabilization: results from the EMF27 scenarios - Gunnar Luderer; Volker Krey; Katherine Calvin; James Merrick; Silvana Mima; Robert Pietzcker; Jasper Van Vliet; Kenichi Wada (Climatic Change, 2014)

Trade-offs between mitigation costs and temperature change - Geoffrey Blanford; James Merrick; Richard Richels; Steven Rose (Climatic Change, 2014)

RETROSPECTIVE ISOTOPIC ANALYSES OF STELLER SEA LION TOOTH ANNULI AND SEABIRD FEATHERS: A CROSS‐TAXA APPROACH TO INVESTIGATING REGIME AND DIETARY SHIFTS IN THE GULF OF ALASKA - Keith A. Hobson; Elizabeth H. Sinclair; Anne E. York; James R. Thomason; Richard E. Merrick (Marine Mammal Science, 2004)
A bstract Stable isotope (δ 15 N and δ 13 C) values of individual tooth annuli of female Steller sea lions ( n = 120) collected from the 1960s through the 1980s were used for retrospective analyses of temporal changes in food webs in the Gulf of Alaska and North Pacific Ocean. We also examined isotopically contour feathers of tufted puffins ( n = 135) and crested auklets ( n = 37) through this period to test for broader isotopic patterns indicative of whole food web changes. Steller sea lions decreased slightly in δ 13 C and increased in δ 15 N values, suggesting an increasing trophic level and change in foraging location or oceanographic isotopic signature. Steller sea lion first and second tooth annuli were enriched in 15 N and depleted in 13 C compared with subsequent annuli, indicating the effects of maternal influence through weaning. The general pattern of increasing δ 15 N values among Steller sea lions supports previous conclusions regarding a reduction or redistribution of forage fishes and an increase of demersal and semi‐demersal species in the North Pacific ecosystem. There were no significant changes in δ 15 N values for either bird species. However, δ 13 C values in both bird species again suggested changes in foraging location or a shift in oceanographic currents.